A False Alibi as a Component of Criminal Activity and Post-Criminal Behavior of the Participants of the Investigation and Assize - ANDREEV, Alexander Sergeevich (Journal of Advanced Research in Law and Economics; Vol 5 No 2 (2014): JARLE Volume V, Issue 2(10), Winter 2014, 2017)
The purpose of the article is to study phenomena, processes and rules of objective reality related to activity (of before, criminal and post criminal period) of crime committers and post criminal behavior of other persons concerned with criminal activities: on reasoning, submission and assertion of a false alibi during inquest and assize, as well as law enforcement agencies activity aimed at disclosure, prevention and revelation of the false alibi. System and comparative approaches and such methods as synthesis and analysis became methodology of the research. In conclusion the final for conducted research notion of the false alibi as a component of the activity of the crime committer and post criminal behavior of persons connected with the crime activities was formulated.